LINEAR ALGEBRA APPLICATIONS TO DETECT THE EXISTENCE OF PLAGIARISM AND IN SEARCH ENGINE METHODOLOGY - Nainggolan, Sahat Pandapotan; Solikhin, Mukhammad; Anwar, Andi Muhammad; Rizki, Nanda Arista (Jurnal Kajian Matematika dan Aplikasinya (JKMA), 2023)
The theory of algebra is highly beneficial and used in daily life. Identifying plagiarism is one of many activities that can be solved with the concept of linear algebra. Even today, plagiarism is still a crucial issue to discuss, preferably in academic scope, both in assignment papers and academic theses. Identifying plagiarism aims to provide a document as a vector. Even the basic concept of linear algebra can be applied in plagiarism detection applications. This paper proposed a modeling example of plagiarism checking on a document with a matrix representation and the calculation of angles among subspaces of each compared document. Finally, the results can be used as one of the considerations to determine the similarity index.Keywords: plagiarism, linear algebra, vector, matrix representation